2023
DOI: 10.1007/s00125-023-05975-8
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2i and GLP-1 RA therapy in type 1 diabetes and reno-vascular outcomes: a real-world study

Matthew Anson,
Sizheng S. Zhao,
Philip Austin
et al.

Abstract: Aims/hypothesis Insulin is the primary treatment for type 1 diabetes. However, alternative glucose-lowering therapies are used adjunctively, but importantly are off-label in type 1 diabetes. Little work has previously been undertaken to evaluate safety with long-term efficacy and cardio-renal benefits of such therapies. We sought to investigate the real-world impact of sodium–glucose cotransporter 2 inhibitor (SGLT2i) and glucagon-like peptide-1 receptor agonist (GLP-1 RA) therapy in individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The SGLT2i-treated cohort showed the preservation of the estimated glomerular filtration rate (eGFR) over a 5-year period compared with the GLP-1 RA-treated cohort (+3.5 vs. −7.2 mL/min/1.73 m 2 ), including patients with established chronic kidney disease (CKD). Moreover, patients treated with SGLT2is were less likely to develop heart failure (relative risk of 0.44) and CKD (relative risk 0.49) when compared to GLP-1RA-treated patients [ 15 ]. A post hoc analysis of the DEPICT trials, two randomised controlled trials investigating the use of dapagliflozin in type 1 diabetes, showed a significant reduction in albuminuria after 1 year of dapagliflozin treatment compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The SGLT2i-treated cohort showed the preservation of the estimated glomerular filtration rate (eGFR) over a 5-year period compared with the GLP-1 RA-treated cohort (+3.5 vs. −7.2 mL/min/1.73 m 2 ), including patients with established chronic kidney disease (CKD). Moreover, patients treated with SGLT2is were less likely to develop heart failure (relative risk of 0.44) and CKD (relative risk 0.49) when compared to GLP-1RA-treated patients [ 15 ]. A post hoc analysis of the DEPICT trials, two randomised controlled trials investigating the use of dapagliflozin in type 1 diabetes, showed a significant reduction in albuminuria after 1 year of dapagliflozin treatment compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Both SGLT2is and GLP-1 RAs have potential benefits as adjunctive agents in T1DM. SGLT2is provide cardio-renal benefits, despite an increase in the risk of DKA, 163 however more studies on T1DM are needed. 164,165 Technologies are T A B L E 5 Cardiovascular-renal outcome trials evaluating novel cardio-renal-metabolic drugs: Overview in relation to haemoglobin A1c (HbA1c) and weight changes.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Both SGLT2is and GLP‐1 RAs have potential benefits as adjunctive agents in T1DM. SGLT2is provide cardio‐renal benefits, despite an increase in the risk of DKA, 163 however more studies on T1DM are needed 164,165 . Technologies are being developed for T1DM by combining risk factors into probability models to predict 10‐year risk for microvascular and macrovascular complications.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 A real-world, global study found 13% of individuals with T1D have taken a non-insulin adjunct for glycemic management, and just 1.7% were prescribed a GLP-1RA off-label. 9 Potential benefits for individuals with T1D include decreased HbA1c, improved glycemic stability, weight reduction, and improved insulin sensitivity and cardiovascular health. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%